Etika Ekologis Islam: Landasan Moral Pemeliharaan Lingkungan Hidup dalam Al-Qur’an dan Hadis - Mike Andrini; Imam Syafei; Baharudin; Ali Murtadho (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The current global environmental crisis demands a moral and spiritual approach to restoring ecological balance. Islam, as a religion that emphasizes justice, responsibility, and harmony, offers a comprehensive ethical framework for environmental preservation. This study aims to analyze the fundamental principles of Islamic ecological ethics derived from the Qur’an and Hadith and to explore their relevance to contemporary environmental issues. The research employs a qualitative approach using library research methods, with thematic analysis of Qur’anic verses, Hadiths, and related scholarly literature. The findings reveal that Islamic ecological ethics are grounded in the values of tawhid (the unity of God and creation), khalifah (human responsibility as guardians of the earth), amanah (trust to protect nature), ‘adl (justice), mizan (balance), and wasathiyah (moderation). These principles guide humans to manage natural resources wisely, fairly, and sustainably. In modern contexts, Islamic ecological ethics are highly relevant to promoting sustainable development, environmental education, and public policies oriented toward ecological preservation. Thus, environmental stewardship in Islam is not merely a social duty but also an act of worship and spiritual devotion to Allah SWT. Keywords: Islamic ecological ethics, Qur’an, Hadith, sustainable development, environment